2020
DOI: 10.1088/1361-6455/ab7078
|View full text |Cite
|
Sign up to set email alerts
|

Superfluid-normal quantum phase transitions in an imbalanced Fermi gas

Abstract: We investigate the superfluid-to-normal zero temperature quantum phase transitions of asymmetric two-component Fermi gases as a function of the chemical potential imbalance h. The calculations are performed for homogeneous and trapped imbalanced systems. We concentrate at unitarity, characterized by a divergent interaction parameter kF a, where most of the current experiments are realized. For homogeneous systems, we determine the critical chemical potential imbalance hc at which possible phase transitions occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 55 publications
(112 reference statements)
0
5
0
Order By: Relevance
“…Comparisons between different theoretical results obtained for the CC limit at unitarity can be found as, for example, in Refs. [47,62,63,71].…”
Section: Effects Of Induced Interactions Corrections To the Tricritic...mentioning
confidence: 99%
See 1 more Smart Citation
“…Comparisons between different theoretical results obtained for the CC limit at unitarity can be found as, for example, in Refs. [47,62,63,71].…”
Section: Effects Of Induced Interactions Corrections To the Tricritic...mentioning
confidence: 99%
“…Our values of y CC for both clean and with impurities are within the results found by means of several theoretical approaches as, for instance, Lobo et al [79], who found (h/µ) c = 0.96 from QMC calculations; Boettcher et al [57], who obtained (h/µ) c = 0.83 by means of the functional renormalization group (FRG). With the FRG they were able to go beyond the mean-field approximation by including bosonic fluctuations on the many-body state; Land et al [47], who found (h/µ) c = 1.09 within a Luttinger-Ward formalism; and (h/µ) c = 0.88 in the work by Caldas [63], obtained by means of thermodynamic equilibrium between possible phases at the unitary limit. We would like to remark in passing, for reference only, that the experimental value obtained for the zero temperature CC limit of a (harmonically trapped) spin-polarized Fermi gas of 6 Li atoms at unitarity is (h/µ) c 0.95 [23,98].…”
Section: Impurity Regimementioning
confidence: 99%
“…[56] Comparisons between different theoretical results obtained for the CC limit at unitarity can be found as, for example, in refs. [47,62,63,71].…”
Section: Effects Of Induced Interactions Corrections To the Tricritic...mentioning
confidence: 99%
“…Our values of yCC$y_{\text{CC}}$ for both clean and with impurities are within the results found by means of several theoretical approaches as, for instance, Lobo et al., [ 79 ] who found false(h/μfalse)c=0.96$(h/\mu )_{\rm c}=0.96$ from QMC calculations; Boettcher et al., [ 57 ] who obtained false(h/μfalse)c=0.83$(h/\mu )_{\rm c}=0.83$ by means of the functional renormalization group (FRG). With the FRG they were able to go beyond the mean‐field approximation by including Bosonic fluctuations on the many‐body state; Land et al., [ 47 ] who found false(h/μfalse)c=1.09$(h/\mu )_{\rm c}=1.09$ within a Luttinger–Ward formalism; and false(h/μfalse)c=0.88$(h/\mu )_{\rm c}=0.88$ in the work by Caldas, [ 63 ] obtained by means of thermodynamic equilibrium between possible phases at the unitary limit. We would like to remark in passing, for reference only, that the experimental value obtained for the zero temperature CC limit of a (harmonically trapped) spin‐polarized Fermi gas of 6Li${}^{6} \rm Li$ atoms at unitarity is false(h/μfalse)c0.95$(h/\mu )_{\rm c} \simeq 0.95$.…”
Section: Effects Of Induced Interactions Corrections To the Chandrase...mentioning
confidence: 99%
“…An ongoing investigation concerns the fate of the paired superfluid in the presence of a spin polarization, with implications for superconductivity in solids. Specifically, at large polarizations, the superfluid is expected to exhibit an instability to a partially polarized or fully polarized normal state [38][39][40][41][42][43][44][45][46][47][48][49].…”
Section: Introductionmentioning
confidence: 99%